2019
DOI: 10.1039/c9bm01077g
|View full text |Cite
|
Sign up to set email alerts
|

AgBiS2-TPP nanocomposite for mitochondrial targeting photodynamic therapy, photothermal therapy and bio-imaging under 808 nm NIR laser irradiation

Abstract: AgBiS2 nanodots as an NIR light-excited photosensitizer produce a PDT effect, which is reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…2 h and Fig. S8 , the photothermal conversion efficiency of Nd@Nd@AgBiS 2 core-shell NPs were calculated to be 45.0%, which was higher than that of most widely studied PTT agents, such as Bi 2 S 3 (26.8%, 28.1%), AgBiS 2 -TPP (23.5%), AgBiS 2 -PEI (21.3%), AgBiS 2 -PEI (35.2%) and AgBiS 2 (36.51%) ( Table S2 ) [ [26] , [27] , [28] , [29] , 36 , 37 ]. The doping of Nd ions facilitated the energy transfer and conversion of the as-prepared core-shell NPs, which could be attributed to the cross-relaxation (CR) process between Nd 3+ ions and AgBiS 2 ( Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…2 h and Fig. S8 , the photothermal conversion efficiency of Nd@Nd@AgBiS 2 core-shell NPs were calculated to be 45.0%, which was higher than that of most widely studied PTT agents, such as Bi 2 S 3 (26.8%, 28.1%), AgBiS 2 -TPP (23.5%), AgBiS 2 -PEI (21.3%), AgBiS 2 -PEI (35.2%) and AgBiS 2 (36.51%) ( Table S2 ) [ [26] , [27] , [28] , [29] , 36 , 37 ]. The doping of Nd ions facilitated the energy transfer and conversion of the as-prepared core-shell NPs, which could be attributed to the cross-relaxation (CR) process between Nd 3+ ions and AgBiS 2 ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, a variety of semiconductors with excellent photothermal conversion abilities, including CuS, Bi 2 S 3 , gold (Au), carbon and metal chalcogenides, have been combined with UCNPs to achieve excellent photothermal and photodynamic efficacy [ [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In particular, bismuth (Bi)-based nanomaterials, such as Bi, Bi 2 S 3 , AgBiS 2 and Bi 2 Se 3, have been proven to be promising candidates as superior photothermal conversion agents, owing to their light absorption coefficient, heat dissipation rate and photothermal conversion efficiency [ [25] , [26] , [27] , [28] , [29] , [30] ]. Furthermore, Bi-based nanomaterials with a narrow band gap can also be used as catalytic materials, which have the ability to generate ROS under light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Highly efficient tumor ablation was further achieved with low cytotoxicity in vitro and in vivo . Sun et al focused on the nanostructure of semiconducting AgBiS 2 and studied the photodynamic activity for cancer treatment . They prepared AgBiS 2 NDs with the size varying from 3 to 12 nm through a solvothermal method and then surface modified with triphenylphosphonium (TPP).…”
Section: Bismuth-based Nanomaterialsmentioning
confidence: 99%
“…Sun et al focused on the nanostructure of semiconducting AgBiS 2 and studied the photodynamic activity for cancer treatment. 142 They prepared AgBiS 2 NDs with the size varying from 3 to 12 nm through a solvothermal method and then surface modified with triphenylphosphonium (TPP). The resulting TPP-AgBiS 2 NDs were also capable of performing PTT with a η value of ∌23.5% at 808 nm.…”
Section: Bismuth-based Nanomaterialsmentioning
confidence: 99%
“…Lei and colleagues reported that TPP-porphyrin photosensitizers with photodynamic activity present significant phototoxicity at concentrations at which "dark toxicity" is negligible towards human breast cancer cells [121]. Also, the AgBiS2-TPP nanocomposite was reported as applicable in photothermal therapy, and it was demonstrated as an agent with high anti-cancer activity [122]. Besides TPP-conjugated drugs, rhodamine derivatives and guanidine-drug conjugates also present as mitochondria-targeting anti-cancer agents that accumulate in mitochondria based on their lipophilic and cationic properties [123][124][125][126][127].…”
Section: Direct Conjugation Of Mitochondria-targeting Ligands To Drugsmentioning
confidence: 99%